Comparative Study: Prophetic Hadith and Qudsi Hadith - Rani Yulisa; Romlah Abubakar Azkar; M. Suparta (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This study examines the comparison between hadith nabawi and hadith qudsi, two categories of hadith that are fundamental in Islam. Hadith nabawi, which are the sayings and actions of the Prophet Muhammad ﷺ, serve as guidelines for the behavior of the people, while hadith qudsi, which are revelations from Allah conveyed through the Prophet, offer a deeper spiritual dimension. Through an analytical approach, this study explores the differences and similarities in the context of the sources, meanings, and practical applications of both. The findings show that although both are rooted in revelation, the differences in wording and context provide unique nuances in the understanding of Islamic teachings. This study is expected to enrich the literature on hadith and provide new insights for Islamic studies.